Economic management in Ireland post-EMU: Ireland?s potential within EMU - Geoghegan, Brian (Statistical and Social Inquiry Society of Ireland, 1999)
A tendency to seriousness is not usually a characteristic associated with the Irish but our national image may be in the process of being redefined as we treat the management of success with almost as much caution and worry as we did the management of the crises of the past. The economy has outperformed all the prognostications ? the Economic and Social Research Institute (ESRI), damned at the time for being over optimistic in its medium-term review, was, as it turned out, far too cautious; the emigration problem has been reversed; standards of living are close to EU average; employment is booming; public finance surpluses are forecast for a number of years and business confidence remains high even if we are at the cusp of this extraordinary period. As we assess the implications of the new monetary and exchange rate straightjacket for our booming economy, it is right that serious reflection be given to the appropriate policy mix for economic management.
Symposium on economic management in Ireland post-EMU
Read before the Society, 18 February 1999
Keywords: Economic management; Economic policy; Globalisation; Irish economic growth; 314.15